The mathematical foundation of informatics : (World Scientific, 2005)
This volume presents research results ranging from those in pure mathematical theory (semigroup theory, graph theory, etc.) to those in theoretical and applied computer science, e.g. formal languages, automata, codes, parallel and distributed computing, formal systems, knowledge systems and database theory.